Mg2+ effects on the single-stranded DNA conformations and nanopore translocation dynamics. (26th May 2022) - Sun, Li-Zhen; Qian, Jun-Lin; Cai, Pinggen; Hu, Han-Xian; Xu, Xiaojun; Luo, Meng-Bo
Abstract: Mg 2+ ion has shown novel merits in the control of the translocation of single-stranded DNAs (ssDNAs) though nanopores. To advance the understanding of the Mg 2+ ion effects on the translocation, it is critical to study the conformational change of ssDNAs under the influence of the Mg 2+ ions and how it affects the translocation dynamics. To this end, a combination of computational simulation and theoretical analysis is used to systematically and thoroughly study the Mg 2+ ion concentration-dependent conformations and translocation dynamics of the ssDNAs with different lengths. The simulation model with originally developed energetic field is validated against previous experiments. Our simulation results reveal that the radius of gyration R g and translocation time τ have the similar behaviors with the changes of ion concentration [Mg 2+ ] and ssDNA length N . The newly reported half-empirical functions are used to predict the ion concentration and ssDNA length-dependent R g and τ, which support the observations in simulations. Both simulation results and quantitative analyses show that for a ssDNA with fixed length N, τ is proportional to R g at different ion concentrations. Moreover, the Flory exponent ν in the scaling law R g  ∼  N ν varies from 0.51 at infinitely high ion concentration to 0.73 in the absence of ions, leading to the change of the scaling exponent α in the scaling law τ  ∼  N α from 1.38 to 1.48 accordingly. On the contrary, the scaling exponent β (= −0.94) in the scaling relationship τ  ∼  f β with f as the driving force is independent of the ion concentrations. Graphical abstract: Image 1 Highlights: [Mg 2+ ]-dependent ssDNA conformation and translocation are studied by LD simulation. High [Mg 2+ ] leads to small radius of gyration and translocation time of the ssDNA. The simulation results can be predicted by the new reported half-empirical functions.